Spatial and temporal vegetation dynamics from 2000 to 2023 in the Western Himalayan regions - Mehmood, Kaleem; Ahmad Anees, Shoaib; Muhammad, Sultan; Albasher, Gadah; Shahzad, Fahad; Hussain, Khadim; Liu, Qijing; Ayub, Rashid; Khan, Waseem Razzaq (Springer Science and Business Media Deutschland, 2025)
This study investigates the interplay of climatic drivers and human activities on vegetation dynamics in the ecologically sensitive Western Himalayas, encompassing Khyber Pakhtunkhwa (KPK), Azad Jammu and Kashmir (AJK), and Gilgit-Baltistan (GB). Using 24 years (2000–2023) of NDVI data from Landsat imagery, advanced techniques, such as the Hurst exponent for long-term persistence and residual trend analysis for isolating anthropogenic impacts, were employed to assess vegetation trends and predict their sustainability. Significant positive trends in NDVI were observed across 20.75% of the area, attributed to afforestation initiatives and conservation efforts, while 56.76% of the region showed no significant change, indicating ecological stability. KPK recorded the highest annual NDVI increase (0.001), driven by afforestation efforts, whereas arid conditions constrained GB’s limited growth (0.00037 annually). Temperature emerged as the dominant climatic driver, influencing 61.53% of the area, with precipitation positively correlating with NDVI in 42.54% of the region. Notably, human activities, including afforestation, contributed to a 28.94% increase in residual NDVI trends, underscoring their pivotal role in vegetation recovery. These findings offer actionable insights for climate-resilient land management, emphasizing the integration of conservation strategies to mitigate the dual impacts of climate change and human activities in mountainous ecosystems.